A novel optical imaging probe for targeted visualization of NLRP3 inflammasomes in a mouse model of age-related macular degeneration - Paguaga, Marcell E.; Penn, John S.; Uddin, MD Imam (Frontiers in Medicine, 2023)
Purpose Wet form of age-related macular degeneration (wet AMD) is a progressive vascular disease that mainly affects older adults and causes severe and irreversible vision loss. A key complication of wet AMD is choroidal neovascularization (CNV), which may be driven in part by NLRP3 inflammasomes that are associated with macrophages migration to CNV lesions. Since activated NLRP3 is correlated with CNV, visualizing NLRP3 inflammasomes and their associated macrophages is of great interest to monitor wet AMD progression and develop effective therapies against it. However, to the best of our knowledge, current ophthalmic imaging systems do not permit such targeted imaging. Therefore, in this study, we developed InflammaProbe-1, an optical imaging probe for targeted visualization of NLRP3 inflammasomes in CNV lesions. Methods InflammaProbe-1 was synthesized by conjugating a clinically relevant fluorophore, Oregon Green® 488, to the selective NLRP3 inhibitor, CY-09. The ability of InflammaProbe-1 to target NLRP3 was assessed with an enzyme-linked immunosorbent assay by comparing its ability to inhibit NLRP3-mediated secretion of IL-1β to that of CY-09 in LPS-primed and nigericin-stimulated BMDMs. In vitro confocal imaging of NLRP3 was performed on InflammaProbe-1-stained BMDMs that had been induced to express NLRP3 with LPS. In vivo imaging of NLRP3 was conducted on mouse laser induced choroidal neovascularization (LCNV), a model of AMD, 6 h after an intraperitoneal injection of InflammaProbe-1 at 10 mg/kg on day 4 post-LCNV. Results InflammaProbe-1 was just as effective as CY-09 at inhibiting IL-1β secretion (p < 0.01 at 10 μM for both the InflammaProbe-1 and CY-09 groups relative to the control). InflammaProbe-1-stained BMDMs that had been induced to express NLRP3 showed significantly brighter fluorescence than untreated cells (p < 0.0001 for LPS treatment group and p < 0.001 for LPS and nigericin treatment group). Furthermore, in vivo molecular imaging of NLRP3 was achieved in mouse LCNV. Conclusion We propose that InflammaProbe-1 may be a useful molecular imaging probe to monitor the onset, progression, and therapeutic response of AMD and other NLRP3-mediated diseases.